Síntese e avaliação biológica de compostos derivados da 5’-arilcalcogenil-3’-amino-timidina - Leal, Julliano Guerin (2020)
Organochalcogen compounds have been the subject of several studies regarding their biological potential in various applications, such as antitumor, antiviral, anti-inflammatory, and antioxidant. Regarding the last, we can highlight its use in combating oxidative stress and its consequences. In this context, ferulic acid is a natural molecule that has a wide variety of biological applications, where we can highlight its ability to act as an antioxidant agent. In the same way, nucleoside analogs have a growing interest in their derivatives for the synthesis of new drugs. On the other hand, the development of new photosensitizers for application in photodynamic therapy has been a very current research target. Among the existing photosensitizers, we can present Rodaminas. Thus, this work had as one of its objectives the preparation of a new class of chalcogen-nucleosides conjugated with ferulic acid. In this work, fifteen chalcogen-nucleoside analogs derived from ferulic acid were synthesized. For this purpose, a protocol was developed using mild conditions, where the said compounds were prepared in good yields (34%-96%). It was found that the studied compounds exhibited anticancer activity in vitro against the bladder cancer cell line, without demonstrating toxic effects in the in vitro assays. performed on mice. They were also tested for their antioxidant capacity in vitro. It was thus observed that the compounds have superior activity in comparison to ferulic acid and all the other standards used. Still, the second objective of this work involved the preparation of photosensitizers applicable to photodynamic therapy derived from rhodamine. In this context, a total of twelve compounds were synthesized, starting from 5'-arylchalcogenyl- 3'-amino-thymidine and rhodamine B, thus obtaining products, in almost all cases, with good yields (14%-96%) and with excellent perspectives aiming their application to PDT, through a simple methodology.